2005
DOI: 10.1016/j.nuclphysa.2005.02.122
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory analysis for fusion path in superheavy-mass region

Abstract: We propose an effective method for the precise investigation of the fusion-fission mechanism in the superheavy-mass region, using the fluctuation-dissipation model. The trajectory calculation with friction is performed in the nuclear deformation space using the Langevin equation. In the reaction 48 Ca+ 244 Pu, the trajectories are classified into the fusion-fission process, the quasi-fission process and the deep quasifission process. By analyzing the time evolution of each trajectory, the mechanism of each pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
75
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(83 citation statements)
references
References 24 publications
8
75
0
Order By: Relevance
“…Even without the quantitative times from the simulations, it is clear from the MAD measurements alone that the dinuclei formed in the Ti and Ni reactions typically rotate less than one turn before scission, which is in quite good agreement with recent theoretical calculations [23,24].…”
supporting
confidence: 81%
“…Even without the quantitative times from the simulations, it is clear from the MAD measurements alone that the dinuclei formed in the Ti and Ni reactions typically rotate less than one turn before scission, which is in quite good agreement with recent theoretical calculations [23,24].…”
supporting
confidence: 81%
“…Although the values of the derivative dσ 2 M /dl 2 are underestimated in comparison with the experimental results [18,19], the main features of the dσ 2 M /dl 2 dependence on the fissility Z 2 /A are reproduced. Many recent works have demonstrated the successful application of the multidimensional Langevin equations to the fission of excited compound nuclei formed in reactions induced by heavy ions [25][26][27][28][29][30][31]. From the physical point of view, the Langevin equations are equivalent to the Fokker-Planck equation, which was widely used for modeling the fission of excited nuclei in the framework of the diffusion model [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…From the spectra, it is found that the mass-symmetric fission fragments do not necessarily originate from fusion-fission, especially for 34 S + 238 U. The symmetric fission fragments without forming the compound nucleus was interpreted as the deep- quasifission [14]. In the mass-asymmetric quasifission, system starts to disintegrate soon after the nuclear contact, and the mass-asymmetry parameter of nuclear shape does not change significantly.…”
Section: Resultsmentioning
confidence: 97%